Characteristics of femur fractures in ambulatory young children. Issue 9 (4th October 2012) - Capra, Louise; Levin, Alex V; Howard, Andrew; Shouldice, Michelle
Abstract : Objectives: To determine and identify the characteristics and circumstances of femur fractures in ambulatory young children. Design and setting: Retrospective review of 203 ambulatory children, between 1 and 5 years old, presenting with femur fractures to an urban paediatric hospital over a 10-year period. χ 2 And Student's t test were employed for statistical analysis. Results: The mean age was 36.6 months, with 155 (76.2%) being male. The most frequent mechanism of injury was fall from a height (n=62, 30.5%). The highest number of injuries occurred in 2–3-year-olds. The most common history in 1–2-year-olds was stumbling on/over something causing a fall. For 4–5 year olds it was road traffic accidents. Other additional physical findings were infrequent (14.3%) and not suspicious of inflicted injury. Child protective services concluded three of the cases to be likely non-accidental, and four cases were inconclusive but requiring close follow-up. Of these seven children, six occurred in 1–2-year-olds. No distinguishing feature was noted in fracture type or location. Conclusions: Femur fractures can occur with low velocity injury whether from a short fall or twisting/stumbling injury in young healthy ambulatory children.